An Fe-doped ZnO/BiVO4 heterostructure-based large area, flexible, high-performance broadband photodetector with an ultrahigh quantum yield. Issue 16 (16th April 2020) - Veeralingam, Sushmitha; Yadav, Pinki; Badhulika, Sushmee
Abstract : Fe doped ZnO/BiVO4 heterostructure based large area, flexible, high-performance broadband photodetector with ultrahigh quantum yield. Abstract : Pristine ZnO has been widely explored for its use in UV photodetectors; however, the utility of ZnO in broadband photodetectors is still a challenge as it absorbs in the UV region only with low quantum efficiency and responsivity that can be accredited to the high recombination rate of photo-generated charge carriers. To address this issue, we report an Fe-doped 2D ZnO thin film, obtained through band gap engineering, and a 1D electrospun mixed-inorganic monoclinic BiVO4 nanofiber heterostructure on an ITO-coated PET substrate-based broadband photodetector (PD) with ultra-high responsivity and EQE values in comparison to PDs fabricated using expensive cleanroom techniques. BiVO4 plays the dual role of absorbing photons in the visible and NIR regions and creating local electric fields at the interface of the Fe-doped ZnO (FZO)–BiVO4 heterostructure, which helps in the separation of electron–hole pairs. The robustness of the flexible PD was further examined under the conditions of repeated bending cycles (up to 500), yielding a stable response. The responsivity values obtained for UV, visible and NIR irradiation are 7.35 A W −1, 3.8 A W −1 and 0.18 A W −1 with very high EQE values of 2501.7%, 851.2% and 28.3%, respectively. The facile and cost-effective fabrication of the device with high performance provides a new approach for developing flexible electronics and high-performance optoelectronic devices.